The Phenomenon of Language Mixing Used among Gen Z in Indonesian Students - Ishak Ishak; Desri Arwen; Euis Yanah Mulyanah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Code-mixing has become increasingly prevalent among Generation Z, particularly in academic and social contexts. This study explored the types of code-mixing used by 8th-semester Gen Z students at Muhammadiyah University of Tangerang, Indonesia, and examined the underlying reasons for this linguistic phenomenon. A qualitative descriptive approach was employed. Data were collected through direct observation of students’ spoken interactions and open-ended interviews conducted at different times. Audio recordings of code-mixing utterances were documented and transcribed for analysis. A total of 177 code-mixing utterances were identified, consisting of three types: insertion (85.3%, 151 instances), alternation (14.7%, 26 instances), and congruent lexicalization (6.2%, 11 instances). The data suggest that insertion is the most dominant form of code-mixing among participants. Several reasons were identified for the frequent use of code-mixing. Students often engage in it unconsciously and see it as a way to improve their English language skills. Additionally, code-mixing is perceived to carry social prestige, making speakers feel confident, proud, and "cool." Social factors—such as peer influence, exposure to trends, and admiration of public figures—also contribute significantly to this behavior. The study reveals that code-mixing among Gen Z students is driven by both linguistic and sociocultural factors. These findings underscore the need to understand code-mixing not merely as a linguistic habit but as a socially influenced form of communication reflective of identity and group belonging.